Bacteraemic pneumococcal pneumonia and SARS-CoV-2 pneumonia: differences and similarities - Serrano Fernández, Leyre; Ruiz Iturriaga, Luis Alberto; España Yandiola, Pedro Pablo; Méndez Ocaña, Raúl; Pérez Fernández, Silvia; Tabernero Huget, Eva; Uranga Echeverria, Ane; Gonzalez Jimenez, Paula; García Hontoria, Patricia; Torres Martí, Antoni; Menendez Villanueva, Rosario; Zalacain Jorge, Rafael (International journal of infectious diseases, 2022)
•In-hospital course and 30-day survival were compared between patients with Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) pneumonia and bacteraemic pneumococcal community-acquired pneumonia (B-PCAP).•B-PCAP was associated with more severe disease on admission and a higher intensive care unit admission rate compared with SARS-CoV-2 pneumonia.•The mortality rate for SARS-CoV-2 pneumonia was higher and deaths occurred later compared with B-PCAP.•Pneumonia severity scales underestimate the risk of death in patients with SARS-CoV-2 pneumonia. To analyse differences in clinical presentation and outcome between bacteraemic pneumococcal community-acquired pneumonia (B-PCAP) and sSvere Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) pneumonia. This observational multi-centre study was conducted on patients hospitalized with B-PCAP between 2000 and 2020 and SARS-CoV-2 pneumonia in 2020. Thirty-day survival, predictors of mortality, and intensive care unit (ICU) admission were compared. In total, 663 patients with B-PCAP and 1561 patients with SARS-CoV-2 pneumonia were included in this study. Patients with B-PCAP had more severe disease, a higher ICU admission rate and more complications. Patients with SARS-CoV-2 pneumonia had higher in-hospital mortality (10.8% vs 6.8%; P=0.004). Among patients admitted to the ICU, the need for invasive mechanical ventilation (69.7% vs 36.2%; P<0.001) and mortality were higher in patients with SARS-CoV-2 pneumonia. In patients with B-PCAP, the predictive model found associations between mortality and systemic complications (hyponatraemia, septic shock and neurological complications), lower respiratory reserve and tachypnoea; chest pain and purulent sputum were protective factors in these patients. In patients with SARS-CoV-2 pneumonia, mortality was associated with previous liver and cardiac disease, advanced age, altered mental status, tachypnoea, hypoxaemia, bilateral involvement, pleural effusion, septic shock, neutrophilia and high blood urea nitrogen; in contrast, ≥7 days of symptoms was a protective factor in these patients. In-hospital mortality occurred earlier in patients with B-PCAP. Although B-PCAP was associated with more severe disease and a higher ICU admission rate, the mortality rate was higher for SARS-CoV-2 pneumonia and deaths occurred later. New prognostic scales and more effective treatments are needed for patients with SARS-CoV-2 pneumonia. [Display omitted]